Does persimmon leaf have a protective effect against oxidative damage caused by chromium in Saccharomyces cerevisiae? - Gok, Ozlem; Beyaz, Seda; Erman, Fazilet; Aslan, Abdullah (Mattioli 1885, 2021)
In this study, 4 groups were formed. Groups; (i) Control group; (ii) Persimmon Leaf Group (10%); (iii) Chromium (K2Cr2O7) Group (10 mM); (iv) Persimmon Leaf (10%) + Chromium (K2Cr2O7) (10 mM) Group. Saccharomyces cerevisiae (S. cerevisiae) cultures were grown at 30 degrees C for 1 hour, 3 hours, 5 hours and 24 hours. Cell growth, lipid peroxidation, MDA (malondialdehyde) analyzes, glutathione (GSH) levels and catalase activities were determined by spectrophotometer. Total protein changes were detected by SDS-PAGE electrophoresis and calculated by the Bradford method. According to the results obtained; cell growth (1, 3, 5 and 24 hours), total protein synthesis (24 hours), GSH levels (24 hours) and catalase activities (24 hours) in the Persimmon Leaf + Chromium group compared to the Chromium group while increasing, MDA level (24 hours) decreased. These results show that persimmon leaf reduces oxidative damage, enhances cell growth and it has a protective effect to promote protein synthesis in S. cerevisiae culture.
Keywords: Cell development; oxidative damage; persimmon leaf; Saccbaromyces cerevisiae; SDS-PAGE